Numerical solution on mixed convection boundary layer flow past a horizontal circular cylinder in a Jeffrey fluid with constant heat flux - Zokri, S. M.; Arifin, N. S.; Mohamed, Muhammad Khairul Anuar; Salleh, Mohd Zuki; Kasim, Abdul Rahman Mohd; Mohammad, Nurul Farahain (AIP Publishing, 2017)
This paper discusses the viscous dissipation effect with constant heat flux on the mixed convection boundary layer flow past a horizontal circular cylinder in a Jeffrey fluid. The transformed partial differential equations are solved numerically by using the well-tested, flexible, implicit and unconditionally stable Keller-box method. Numerical results for the velocity and temperature profiles are attained in the form of graph for different values of parameters such as Prandtl number, ratio of relaxation to retardation times and Deborah number. It is found that the velocity profile is noticeably decreased with an increase in Deborah number while the temperature profile is slightly increased.